FEATURES OF INTENSIVE NUTRITIONAL SUPPORT OF PREMATURE INFANTS IN THE POSTRESUSCITATION PERIOD AFTER DISCHARGE FROM HOSPITAL (PART 2) - K.V. Romanenko; A.P. Averin; A.F. Kiosov; A.I. Gaeva; N.Yu. Bogachev (Педиатрическая фармакология)
This review considers specific problems of premature infants in the first year of life related to nutritional deficiencies and lack of basic food nutrients. The features of nutritional support of premature infants who underwent resuscitation phase in the first year of life, the usefulness of the new «mixes for premature infants, discharged from the hospital» in order to intensify the programming power of artificial feeding are discussed. Key words: preterm infants, very low body weight, extremely low body weight, intensive care and neonatal intensive care, enteral nutrition, special mixtures for premature, «the mixture for premature infants, discharged from the hospital». (Pediatric Pharmacology. — 2011; 8 (5): 91–96.)